2020
DOI: 10.2147/tcrm.s192392
|View full text |Cite
|
Sign up to set email alerts
|

<p>Updated Evaluation of Dupilumab in the Treatment of Asthma: Patient Selection and Reported Outcomes</p>

Abstract: Uncontrolled asthma continues to be a problem for many patients with moderateto-severe allergic asthma. Dupilumab, which blocks the receptors for interleukin-4 and interleukin-13, has been effective in reducing asthma exacerbations, improving forced expiratory volume in one second (FEV 1), and reducing oral corticosteroid use. When selecting patients for dupilumab, it is important to consider entry criteria for the original studies, subgroups that have responded best, and the presence of comorbid diseases that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…In the clinic, it may be observed that Fe NO remains high in these patients during anti-IL-5 treatment, despite the reduction in eosinophils [28,29]. Similarly, anti-IL-4Rα treatment can reduce Fe NO , but transient eosinophilia may be observed [8]; caution should therefore be taken when considering anti-IL-4Rα for patients with a history of hypereosinophilic conditions [30]. Alternatively, mixed granulocytic asthma may be present, in which there are elevated levels of both eosinophils and neutrophils [24].…”
Section: Inflammatory Pathways In Asthmamentioning
confidence: 99%
“…In the clinic, it may be observed that Fe NO remains high in these patients during anti-IL-5 treatment, despite the reduction in eosinophils [28,29]. Similarly, anti-IL-4Rα treatment can reduce Fe NO , but transient eosinophilia may be observed [8]; caution should therefore be taken when considering anti-IL-4Rα for patients with a history of hypereosinophilic conditions [30]. Alternatively, mixed granulocytic asthma may be present, in which there are elevated levels of both eosinophils and neutrophils [24].…”
Section: Inflammatory Pathways In Asthmamentioning
confidence: 99%
“…Some investigators have suggested that the occurrence of EN is a contraindication to further use of dupilumab, but a correlation between the drug and the adverse event cannot be confirmed without re-exposure. 11 In consultation with the Allergy Department, it was decided to restart dupilumab, given the remarkable improvement in asthma symptoms. The temporal relationship between the initiation of dupilumab treatment and onset of the EN eruption, improvement after discontinuation, and recurrence after rechallenge, suggests a potential correlation between dupilumab and EN.…”
Section: Discussionmentioning
confidence: 99%
“…Transient eosinophilia in patients treated with dupilumab was observed in a few studies as compared with placebo. This is believed to be caused by the reduction in the dose of glucocorticoids and blocking eosinophil migration into the tissue through the inhibition of IL-4- and IL-13-mediated eotaxins and vascular adhesions 39 . It is important to note that dupilumab does not directly affect the eosinophil synthesis; hence, no long-term effects on eosinophil counts are expected 19 .…”
Section: Discussionmentioning
confidence: 99%